Training in Depression Symptom Recognition and Positive Thinking to Prevent Suicide - Ningrum, Dwi Arimbi Setia; Putri, Ainayya Alfatihah; Pranawengrum, Ratri Ayu; Brigianto, Alphecca Carinae; Situmorang, Nina Zulida (Unram Journal of Community Service, 2025)
Suicide is a complex phenomenon often associated with depression, local myths, and limited mental health services. Gunungkidul Regency, Special Region of Yogyakarta, has a high suicide rate, often associated with the myth of pulung gantung. Depression is a major factor, exacerbated by the lack of access to mental health services and low public health literacy. This study aims to increase community awareness about the symptoms of depression, provide education about positive thinking to prevent depression and suicide, and develop an intervention strategy based on education and discussion. The method used in this study is quantitative method. Pretest and post-test data were analyzed to evaluate changes in participants' knowledge of depressive symptoms and the importance of positive thinking after the training. The results of paired sample t-test analysis showed a significant increase in depression and positive thinking variables after the training. The mean depression score increased from 65 (pre-test) to 94 (post-test) with a t value = -14.447 and significance <0.001 (p<0.01). The mean value of the positive thinking variable also increased from 66 to 95 with a t value = -21.244 and significance <0.001 (p<0.01). This study proves that psycho education training in Wareng Village is effective in improving people's understanding of the symptoms of depression and the importance of positive thinking.